OCEANS 2015 - Genova 2015
DOI: 10.1109/oceans-genova.2015.7271562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on signal attenuation at microwaves frequencies underwater

Abstract: New wireless applications are emerging subsea. Pinless Subsea Connectors (PSC) aim to transfer high-speed data over short distances. They present several advantages in comparison with previous technologies. However, its design presents several challenges that need to be addressed. For PSC based on electromagnetic signaling, one of the principal factors affecting system planning is signal attenuation. This work characterizes the impact of water temperature on signal attenuation in both freshwater and seawater. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…represents angular frequency, represents dielectric permittivity at low frequency, ∞ is the dielectric permittivity at high frequency and represents the relaxation time [4].…”
Section: Microwave Signal Propagation In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…represents angular frequency, represents dielectric permittivity at low frequency, ∞ is the dielectric permittivity at high frequency and represents the relaxation time [4].…”
Section: Microwave Signal Propagation In Watermentioning
confidence: 99%
“…Underwater radio propagation is also affected by temperature. In seawater, conductivity increases with temperature due to increased ionization, leading to higher losses with increasing temperature, whereas in freshwater, the loss factor decreases as temperature increases [4].…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency electromagnetic waves cannot be used for communication over long distances underwater due to high attenuation. In the frequency range from 1 to 3.5 GHz, the power of electromagnetic radiation is attenuated by 50 dB at a distance of about 10 cm [6]. At a frequency of 800 MHz, the attenuation of the RF signal is about 70 dB at a distance of 1 m [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some developments have shown that the 2.4 GHz band is of tremendous interest for several configurations [12][13][14]. Previous studies have demonstrated the potential of this band in terms of signal propagation under several conditions [15,16].…”
Section: Introductionmentioning
confidence: 99%